2018
DOI: 10.31219/osf.io/s3cm4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exaggerated expectations in ancient starch research and the need for new taphonomic and authenticity criteria

Abstract: Document VersionPublisher's PDF, also known as Version of record Citation for published version (APA):Mercader, J., Akeju, T., Brown, M., Bundala, M., Collins, M. J., Copeland, L., ... Xhauflair, H. (2018). Exaggerated expectations in ancient starch research and the need for new taphonomic and authenticity criteria. FACETS, 3, AbstractAncient starch research illuminates aspects of human ecology and economic botany that drove human evolution and cultural complexity over time, with a special emphasis on past te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
5
0
4
Order By: Relevance
“…Major observations were the absence direct morphometric markers within 14 of the 31 screened families. The study concluded that morphological parameters were not concrete enough to establish taxonomic identification [4]. Properties of starch grains such as size, structure and shape extracted from various plant sources differ only to a certain extent, such that starches from some different biological sources can be identified.…”
Section: Morphological and Micrometric Properties Of Starch Granulesmentioning
confidence: 97%
See 2 more Smart Citations
“…Major observations were the absence direct morphometric markers within 14 of the 31 screened families. The study concluded that morphological parameters were not concrete enough to establish taxonomic identification [4]. Properties of starch grains such as size, structure and shape extracted from various plant sources differ only to a certain extent, such that starches from some different biological sources can be identified.…”
Section: Morphological and Micrometric Properties Of Starch Granulesmentioning
confidence: 97%
“…β-amylose has a helical arrangement comprising of six glucosyl units and a diameter of 1.3 mm. The differences in the structure and proportion or amounts of amylopectin and amylose give starch grains different properties and add immensely to the distinctive properties of starch from various sources [1][2][3][4][5][6][7][8][9].…”
Section: Starch and Formation Of Starch Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers in the field are working towards better methods for establishing authenticity criteria for ancient starches, including exploring the potential for molecularly identifying starches, and understanding the taphonomic pathways by which starches may be preserved (Mercader et al 2018) .…”
Section: Contamination Modern and Ancientmentioning
confidence: 99%
“…A palaeoanthropological project that recognises such issues is Stone Tools, Diet, and Sociality (SDS), a palaeoanthropological partnership between environmental specialists, biologists, geologists, social scientists, and palaeoanthropologists from institutions located in numerous countries. SDS's interdisciplinary collaborations are producing myriad new insights that are vital for understanding humanity's emergence (Favreau 2019;Mercader et al, 2018a;Mercader et al, 2018b;Mercader et al, 2019;Soto et al, 2019;Soto et al, 2020a;Soto et al, 2020b;Tucker 2018;Tucker et al, 2020). Furthermore, SDS aspires to curb the history of neocolonial research at Oldupai by collaborating with the local Maasai, and Maasai peoples shared in such desires for collaboration.…”
Section: The World Bank and The International Monetarymentioning
confidence: 99%